Validation of Radiocarbon Dates of Woolly Mammoth Remains from Northwestern Chukotka, Russia - Vartanyan, Sergey L (Radiocarbon, 2013)
This paper presents the results of cross-dating of mammoth remains from northwestern Chukotka, northeastern Siberia. Our results suggest that several dates obtained by the radiocarbon laboratory at the Institute of Geology and Mineralogy, Siberian Branch of the Russian Academy of Sciences, Novosibirsk (laboratory code SOAN) appear to be too recent. Cross-dating in different laboratories revealed significant differences in the ages obtained compared to SOAN. This highlights the need to critically assess 14 C dates, and where necessary, confirm results in independent laboratories.